Emergence of magnetic order and enhanced magnetoelectric coupling in Lu-doped Sm2BaCuO5. Issue 7 (1st April 2022) - Zhou, G.Z.; Min, J.H.; Tang, Y.S.; Chen, X.Y.; Gong, J.W.; Lin, L.; Liu, M.F.; Huang, L.; Zhang, J.H.; Zheng, S.H.; Yan, Z.B.; Zeng, M.; et al.
Abstract: The green-phase compound Sm2 BaCuO5 has recently drawn significant attention due to the prominent linear magnetoelectric (ME) coupling effect. Herein, we report a successful chemical doping control of magnetic order and ME effect in Lu 3+ -doped multiferroic Sm2 BaCuO5 . Upon a small amount of Lu 3+ doping, it is suggested that the majority of Cu ions interact through Sm 3+ and order at T N1 ∼ 23 K, whereas some Cu 2+ interacting through Lu 3+ can lead to another transition at T * ∼21 K–16 K upon doping Lu 3+ ions from 5% to 20%. More interestingly, this emergent magnetic order is concomitant with a broad valley in the pyroelectric current and dielectric anomaly, providing clear evidence of intrinsic coupling between magnetic and ferroelectric orders. In contrast to the parent phase, significant enhancement of the linear ME coefficient is obtained. Our results unveil the importance of interplay of 4 f -3 d magnetic interactions in inducing ferroelectricity and offer an alternative route to achieve high performance in ME coupling.